Association between air pollution and lifestyle with the risk of developing mild cognitive impairment and dementia in individuals with cardiometabolic diseases - Bo Wang; Lingling Yang; Ting Ma; Shulan He; Jiangping Li; Xian Sun (Scientific Reports)
Abstract Lifestyle factors and ambient air pollution are linked to dementia and CMDs, yet few studies have investigated their impact on dementia risk in CMDs patients at the same time. The Cox proportional hazards model was used to evaluate the influence of lifestyle and ambient air pollution on the dementia risk of the CMDs population among 438,681 participants in the UK Biobank. It is found that the risk of developing mild cognitive impairment and dementia in the population seems to increase with the increase in the number of CMDs. There appears to be a statistically significant association between high levels of ambient air pollution, unhealthy lifestyles, and a higher risk of developing mild cognitive impairment and dementia in the CMDs population. It is found that a healthy lifestyle may have an effect modifier role in the association between ambient air pollution and the risk of mild cognitive impairment and the development of dementia in patients with CMDs. Therefore, maybe people with CMDs can lessen the impact of ambient air pollution on their risk of developing mild cognitive impairment and dementia by improving their lifestyle.